2021
DOI: 10.3390/md19120668
|View full text |Cite
|
Sign up to set email alerts
|

A Novel C1q Domain-Containing Protein Isolated from the Mollusk Modiolus kurilensis Recognizing Glycans Enriched with Acidic Galactans and Mannans

Abstract: C1q domain-containing (C1qDC) proteins are a group of biopolymers involved in immune response as pattern recognition receptors (PRRs) in a lectin-like manner. A new protein MkC1qDC from the hemolymph plasma of Modiolus kurilensis bivalve mollusk widespread in the Northwest Pacific was purified. The isolation procedure included ammonium sulfate precipitation followed by affinity chromatography on pectin-Sepharose. The full-length MkC1qDC sequence was assembled using de novo mass-spectrometry peptide sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…The protein was detected in association with connective tissue fibers in mantle edge and digestive glands, in kidney concretions, as well as in interstitial space and the hemal system of all organs. Thus, the most intensively labeled organs were gills and pericardium with largest hemal sinuses and vessels [61]. The reason for such a distribution can be the same as in the SghC1qDC case because MkC1qDC is also a soluble protein.…”
Section: Biosynthesis and Tissue Distribution Of C1qdc Proteinsmentioning
confidence: 85%
See 2 more Smart Citations
“…The protein was detected in association with connective tissue fibers in mantle edge and digestive glands, in kidney concretions, as well as in interstitial space and the hemal system of all organs. Thus, the most intensively labeled organs were gills and pericardium with largest hemal sinuses and vessels [61]. The reason for such a distribution can be the same as in the SghC1qDC case because MkC1qDC is also a soluble protein.…”
Section: Biosynthesis and Tissue Distribution Of C1qdc Proteinsmentioning
confidence: 85%
“…Most of the studied C1qDC proteins have been obtained in recombinant form. Only a few C1qDC proteins have been isolated and described in their native forms, such as SghC1qDC (OXYL) from the feather lily Anneissia japonica [25] and MkC1qDC recently isolated by us from the mussel Modiolus kurilensis [61]. The linear domain structure of C1qDC proteins was determined using SMART [62] (Figure 2).…”
Section: C1qdc Proteins' Structures and Phylogenymentioning
confidence: 99%
See 1 more Smart Citation
“…The function between the C1q protein and adiponectin is different in mammals: they complement system and glucose-level regulation, respectively. In molluscs, several C1q-related and C1q-domain-containing proteins were isolated, and these proteins are suggested to be involved in molluscan immune systems [ 24 , 25 , 26 ]. However, in mammals, adiponectin can bind with the C1q complex and activate the classical complement pathway [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Grinchenko, Kriegsheim, Shved et al, have reported the biochemical properties of the novel C1q domain containing protein, MkC1qDC, from the hemolymph of the bivalve mollusk Modiolus kurilensis [ 10 ]. MkC1qDC showed a lectin-like activity by binding galactose and mannose with a requirement of Ca2+.…”
mentioning
confidence: 99%